2017
DOI: 10.1111/ene.13378
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐dependent effects of uric acid on cerebral microbleed: a cross‐sectional study in the general population

Abstract: High serum UA value was associated with higher prevalence of CMB in male, but lower prevalence of CMB in female subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This also may reflex the dual effect of UA. In a cross-sectional study of 2,686 patients, Jeong et al reported that a high UA level was a risk factor for cerebral microbleeds only in male patients (19), and we confirmed and extended this finding in our study. Further studies are needed to explore whether these patients are potential candidates for interventions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This also may reflex the dual effect of UA. In a cross-sectional study of 2,686 patients, Jeong et al reported that a high UA level was a risk factor for cerebral microbleeds only in male patients (19), and we confirmed and extended this finding in our study. Further studies are needed to explore whether these patients are potential candidates for interventions.…”
Section: Discussionsupporting
confidence: 90%
“…UA levels are commonly available in medical settings, and the results of our study suggested that UA may be a potential target for interventions. Several previous studies have investigated the sex differences of UA in patients with cerebrovascular diseases (19,20). Recently, a similar study reported that the incidence of spontaneous HT was higher in patients with low UA levels than in patients with high UA levels (13).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke remains the most common problem for neurologists to diagnose and treat . Preventative measures, such as control of hypertension, reduction in smoking and treatment of hyperlipidaemia, have made a significant contribution to preventing and delaying stroke onset.…”
mentioning
confidence: 99%